To correctly demonstrate polynomial addition, we need to combine like terms properly. Let's analyze the provided responses:
-
(2x² + 6x + 1) + (3x² + 3x + 9) = 13x² + 9x + 10
- This is incorrect. The correct addition of the terms should be:
- \(2x² + 3x² = 5x²\)
- \(6x + 3x = 9x\)
- \(1 + 9 = 10\)
- Therefore, the left side should equal \(5x² + 9x + 10\).
- This is incorrect. The correct addition of the terms should be:
-
(2x² + 6x + 1) + (3x² + 3x + 9) = (2x² + 3x + 1) + (3x² + 6x + 9)
- This is also incorrect because it does not perform the addition; instead, it rearranges the terms without correctly equating them.
-
(2x² + 6x + 1) + (3x² + 3x + 9) = 5x⁴ + 9x² + 10
- This is incorrect. The degree of polynomial terms is miscalculated. The addition should not produce a term of \(5x^4\) as there are no \(x^4\) terms in either polynomial.
-
(2x² + 6x + 1) + (3x² + 3x + 9) = 5x² + 9x + 10
- This is correct. As shown in the calculations above, the like terms were appropriately added together.
-
(2x² + 6x + 1) + (3x² + 3x + 9) = -x² + 3x - 8
- This is incorrect. The signs and values do not match up with the expected results from the addition.
Thus, the correct response that demonstrates polynomial addition is:
(2x² + 6x + 1) + (3x² + 3x + 9) = 5x² + 9x + 10.